Methods of onfarm, diagnostic research on adoption potential of alley cropping - Dvořék, K.A. (1991)
An approach to on-farm diagnostic research on alley cropping is described. The objective of economic assessment was to evaluate the adoption potential of the technology. Three activities were included. In the first research activity, cost-route surveys and field measurements were carried out for a small sample of farmers with recently established alleys. Although research-resource intensive, the cost-route studies and field measurements were necessary to develop a framework for analyzing alley cropping on-farm because rapid methods of assessing intrinsically dynamic technologies are not yet available. Administration of a focused, formal single visit survey to a large sample of farmers who have participated in alley farming trials at several locations was the second activity. Intensive data collection with a small sample continued in order to quantify factors identified as key in the first activity. Although still developmental, it is hoped that the combination of methods will contribute to development of more rapid and readily accessible methods of evaluating agroforestry technologies on-farm.